ANALISISI KEPUASAN KERJA DAN LINGKUNGAN KERJA TERHADAP INDIKASI LABOUR TURNOVER PADA TENAGA KEPENDIDIKAN UNIVERSITAS LANCANG KUNING, PEKANBARU - Lubis, Nurhayani; Hendriani, Susi (Jurnal Ekonomi Bisnis Kompetif, 2023)
This study aims to determine: (1) The effect of job satisfaction on labor turnover in teaching staff at Lancang Kuning University, Pekanbaru, (2) The effect of the work environment on labor turnover in teaching staff at Lancang Kuning University, Pekanbaru, (3) The effect of job satisfaction and the environment work on labor turnover in Lancang Kuning University educational staff, Pekanbaru. Using a quantitative approach, the subject of this research is the education staff at Lancang Kuning University. Data collection used questionnaires and interviews while data analysis was carried out using multiple linear regression analysis. The results showed that the variables of job satisfaction and work environment had a significant effect on labor turnover in educational staff at Lancang Kuning University. Likewise with the joint test, the results of both had a significant effect. For the results of the coefficient of determination, the test results show that the percentage of labor turnover for the variables of job satisfaction and work environment is 34.8%.